Price Discovery Pada Pasar Obligasi Pemerintah Indonesia - Wibowo, Buddi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 2 Tahun 2021, 2021)
Th e study investigat e price discovery in Indonesia government bond market. Understanding p rice discovery is a must to identify relevant factor affecting price of the asset. This research will cover two tier market, first tier is interdealer market and second tier is  customer market. We study the dealer and customer order flow to identify which side that have greater impact in price formation in government bond market. The results show that from the two layers of order flow, the short-term dealer order flow and short-term customer order flow have role in price discovery process. Customer flow order regression coefficient is larger than the dealer order flow. Customers trade not only trade based on liquidity but also have information in making decisions or making investment portfolios (informed customers). At the group dealer order flow, dealers have a heterogeneous role and have different segments.